Reproductive Diseases and Disorders of Female Camels: An Assessment and Pathological and Bacteriological Study in Eastern Ethiopia - Dinaol Belina; Amare Eshetu; Sisay Alemu; Bekyad Shasho; Tajudin Mohammed; Ahmedin Mohammed; Bahar Mummed; Dereje Regassa (Veterinary Medicine International)
Camels are the most efficient domesticated animals in arid and semiarid areas of the world. In Ethiopia, they are the main livestock kept to sustain the livelihoods of pastoralists, as camels are used for milk and meat production and also for transportation. However, she-camel reproductive diseases are one of the major constraints for camel-producing communities. A cross-sectional study was conducted from November 2018 to December 2019 to identify and characterize pathological lesions and isolate possible bacteria associated with reproductive diseases and disorders in she-camels slaughtered at Dire Dawa and Babille municipal abattoirs. A total of 155 study animals were examined by recruiting all she-camels slaughtered during every abattoir visit. Overall, 562 reproductive organs, the ovaries, oviducts, uterus, and cervix, were examined through observation, palpation, and incision, and the animal- and organ-level pathological lesion prevalence were found to be 29% and 64.6%, respectively. Degenerative changes, inflammatory lesions (endometritis and salpingitis), growth disturbances (e.g., ovarian hypoplasia), and noninflammatory lesions (e.g., noninflammatory edema) were the identified pathological lesions. Occurrences of pathological changes among reproductive organs had differences where significantly the highest proportion (p = 0.00) was observed in the uteri. Of the 119 microbiological samples processed, 77.3% were positive for single or mixed bacterial genera, from which 7 different bacterial isolates and 14 other unidentified Gram-negative bacteria were detected. E. coli, Salmonella, and Staphylococcus spp. were the most frequently isolated organisms with 28.2%, 26.9%, and 12.8% frequencies, respectively. The result of the questionnaire survey showed 74% of the respondents had culled the she-camel at productive age because of poor reproductive performance associated with refused mating, abortion, and repeat breeding (poor conception). On the other hand, a majority of camel herders had poor to no information and access to modern veterinary services; nevertheless, they had good indigenous knowledge on how to manage reproductive abnormalities. Considering the importance of camels in our study area, further research on camel reproductive diseases and abnormalities with wider sample and epidemiology need to be conducted using molecular and hormonal assay techniques.